2020
DOI: 10.1111/1467-8268.12410
|View full text |Cite
|
Sign up to set email alerts
|

The impact of terrorism on public debt in African countries

Abstract: Given the increase in the number of terrorist attacks in African countries, a better understanding of the relationship between terrorism, the informal economy and public debt is essential for policymakers. The model is empirically tested for 47 countries during the period 1996–2015. We use ordinary least squares (OLS), random effects (ER) and system generalized method of moments (GMM). Three terrorism indicators are used: the uncertain, the domestic, and the transnational. The results confirm that the rise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
1
12
0
2
Order By: Relevance
“…Furthermore, our estimates are indicating that, the arms imports have a positive and significant impact on public debt. This is in line with the study of Abid and Sekrafi (2020), who investigates the impact of terrorism on public debt in African countries. Authors found that, the rise in terrorism and military expenditure lead to an increase in public debt in Africa.…”
Section: Panel Data Estimatessupporting
confidence: 85%
“…Furthermore, our estimates are indicating that, the arms imports have a positive and significant impact on public debt. This is in line with the study of Abid and Sekrafi (2020), who investigates the impact of terrorism on public debt in African countries. Authors found that, the rise in terrorism and military expenditure lead to an increase in public debt in Africa.…”
Section: Panel Data Estimatessupporting
confidence: 85%
“…Total terrorism is the sum of domestic, transnational and unclear terrorism. These four terrorism indicators are increasingly used in the literature on terrorism (Abid & Sekrafi, 2020; Asongu & Nwachukwu, 2017). For robustness, we have used two other measures of terrorism from the Global Terrorism Database (GTD, 2018) database: these are (a) the number of terrorist attacks; and (b) the number of deaths due to terrorism.…”
Section: Methodsmentioning
confidence: 99%
“…When looking at the causes of terrorism, the literature on terrorism shows that this proliferation of terrorist groups is linked particularly to the high level of corruption, the failure of governments, the abundance of natural resources, ethnic and tribal tensions, religious fundamentalism and political instability (Alfa‐Wali et al, 2015; Anyanwu, 2014; Asongu et al, 2019; Fazel, 2013; Tahir et al, 2019). Regarding the socioeconomic and political consequences of terrorism, it has been empirically demonstrated in the literature that terrorism has an adverse effect on foreign direct investment (Ezeoha & Ugwu, 2015), governance (Asongu & Nwachukwu, 2017), public debt (Abid & Sekrafi, 2020), trade (Nitsch & Schumacher, 2004), water access (Gleick, 2006) and more importantly economic growth (Abadie & Gardeazabal, 2003; Choi, 2015; Yapatake Kossele & Shan, 2018; Younas, 2015). Surprisingly, the question of whether terrorism affects agriculture has received little attention, particularly in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…After the sale of illegal oil, the trade of antiquities still represents the second source of financing for the ISIL group. The global illegal trade in endangered species generates $ 7 to $ 10 billion in revenue, and terrorists living in areas close to protected and endangered wildlife benefit from this market (Abid & Sekrafi, 2020). For example, al‐Shabaab used profits from the informal ivory trade to finance terrorist attacks in Kenya.…”
Section: Introductionmentioning
confidence: 99%